Pengukuran Kecepatan Rambat Gelombang Ultrasonik untuk Menentukan Komposisi Tanah pada Lapisan Gradasi - Darmawan, Dudi; Suprayogi, Suprayogi; Muzayyanah, Nur Indah (Universitas Trunojoyo Madura, 2022)
Information on soil type and thickness becomes important in planning land use for various purposes, both agriculture and infrastructure. Measurements to identify this information have been developed using various methods, one of which is the ultrasonic wave method. However, the measurement of the thickness of the soil layer is carried out by knowing the speed of wave propagation in the layer. Generally, in various measurements, the assumption of a constant ultrasonic wave propagation speed is used. However, in various situations where the layers have mixed to form a gradation layer, it is necessary to characterize the soil first. This study aims to characterize the graded soil layer by measuring the speed of ultrasonic waves at conditioned thickness. The composition of the gradation layer was varied and the speed of propagation was measured. The results show that the composition of the soil in the gradation layer affects the ultrasonic wave propagation speed quite linearly. Experiments carried out on variations in the composition of lembang soil, laterite and humus showed a linear relationship with an average coefficient of determination of 0.978 and the results of testing the function of soil composition in the gradation layer to the speed of wave propagation resulted in an average error of 1.32%.